2010
DOI: 10.1002/ppul.21331
|View full text |Cite
|
Sign up to set email alerts
|

Do New Zealand children with non‐cystic fibrosis bronchiectasis show disease progression?

Abstract: In our experience despite management in a tertiary multidisciplinary bronchiectasis clinic, progression of lung disease continues in a group of children and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 37 publications
3
45
0
1
Order By: Relevance
“…However, other studies also report S. pneumoniae in <10 % of respiratory cultures from NZ children with bronchiectasis [22,23], which contrasts with rates of 29-43 % reported in young healthy or otitis-prone NZ children [24]. Although S. pneumoniae carriage was lower in the azithromycin groups, it had recovered by the end of the Fig.…”
Section: Carriage and Resistance During The Interventionmentioning
confidence: 52%
“…However, other studies also report S. pneumoniae in <10 % of respiratory cultures from NZ children with bronchiectasis [22,23], which contrasts with rates of 29-43 % reported in young healthy or otitis-prone NZ children [24]. Although S. pneumoniae carriage was lower in the azithromycin groups, it had recovered by the end of the Fig.…”
Section: Carriage and Resistance During The Interventionmentioning
confidence: 52%
“…While pediatric bronchiectasis mortality data from developing countries are limited, a Malaysian study observed considerable morbidity with a negative impact upon growth, lung function, and quality of life (QoL) . Similar adverse effects were observed in New Zealand Maori and Pacific Island children, despite receiving treatment at a tertiary center, while in contrast in children from England treatment stabilized lung function . Furthermore, bronchiectasis has been associated with increased cardiac morbidity, malnutrition, osteopenia, and even cancer …”
Section: Burden Of Diseasementioning
confidence: 97%
“…Of the 5,745 deaths attributed to bronchiectasis in England and Wales between 2001 and 2007, only 12 were in the 0–14 year age group . In contrast 6 (7%) of 91 children (59% Pacific Island, 24% Maori) with bronchiectasis died while attending a single New Zealand center between 1991 and 2006 . Importantly, the premature mortality in high‐risk pediatric populations carries over into adulthood.…”
Section: Burden Of Diseasementioning
confidence: 99%
“…[21][22][23] In most studies, the average age at diagnosis of bronchiectasis was 5 to 9 years, but all series included children diagnosed at , 1 year of age. 4,[23][24][25] One-half of the children in our study were , 3 years old at enrollment, and our report represents a unique insight into the longitudinal course of children with CSLD/bronchiectasis diagnosed early in life.…”
Section: Predisposing Factors For Recurrent and Severe Aresmentioning
confidence: 99%